The Challenges of Adolescent Education in the Context of Early Marriage: Seeking Solutions to Improve Access and Participation - Islam, Ala’ul; Zaini, Muyassaroh (Jurnal Ilmiah Profesi Pendidikan, 2023)
Early marriage is one of the factors that hinder access and participation in adolescent education, especially in developing countries. This results in low graduation rates, increased health risks, and limitations on opportunities for adolescents to reach their full potential. This study aims to analyze the challenges of adolescent education in the context of early marriage and seek solutions to improve access and participation. The research adopts a qualitative approach with descriptive analysis. Data were collected through literature reviews and case studies from several countries facing early marriage issues. Data were obtained through searches of relevant literature, interviews with education and health experts, and policy document analysis. Data were analyzed thematically, considering patterns emerging from the collected data. The research findings identified several key challenges in adolescent education related to early marriage, including limited access, social pressures, and lack of support from families and communities. Proposed solutions include improving access to education, awareness campaigns, and training for educators and communities. This study has significant implications for efforts to enhance access and participation in adolescent education amidst the challenges of early marriage. Practical implications include the development of supportive policies, integrated intervention programs, and collaborative approaches among governments, educational institutions, and civil society.